Real-Time Marketing - Ledzian, Paulina (Funkcjonowanie e-biznesu. Zasoby, procesy, technologie, 2015)
In order to effectively promote a product or brand it is necessary to adapt to the requirements of the market and the customer. The modern customer who is accustomed to receiving everything up to date is not used to waiting and requires far more than customers a dozen years ago. Therefore, the response in real time on what is happening in the world from monitoring the activities of competition through cultural events to the news of the world is very important for companies that want to keep up with their clients. Personalized, dynamic content created by brands and skilful, quick response to current pop-culture phenomenons is referred to as the Real-Time Marketing. Companies worldwide are increasingly turning to Real-Time Marketing strategy, which enables large profits at a disproportionately low investment.